Ad hoc networks : Third International ICST Conference, ADHOCNETS 2011, Paris, France, September 21-23, 2011 : revised selected papers - Simplot-Ryl, David 1970-; Dias De Amorim, Marcelo; Giordano, Silvia; Helmy, Ahmed Abdel-Ghaffar; International Conference on Ad Hoc Networks 2011 Paris, Francia (Heidelberg : Springer, 2012)
This volume constitutes the refereed proceedings of the Third International ICST Conference, ADHOCNETS 2011, held in Paris, France, in September 2011. The 15 revised full papers - selected from 42 submissions - and the 2 invited papers cover several fundamental aspects of ad hoc networking, including security, quality of service, radio and spectrum analysis, mobility, energy efficiency, and deployment. They are organized in topical sections on security and QoS, WSN development and evaluation, radio and spectrum analysis, mobile WSNs, mobile ad hoc networks, and energy.
Keywords: REDES AD HOC (REDES DE COMPUTADORAS) -- CONGRESOS; REDES DE COMPUTADORAS -- CONGRESOS